The Surface EMG Characteristics between Erector Spinae and Vastus Lateralis during Bending Forward and Squatting Down Tasks. (19th October 2015) - Xiao, Jinzhuang; Gao, Junmin; Wang, Hongrui; Liu, Kun; Yang, Xincai
Abstract : Bending forward and squatting down are two common physical tasks in everyday life and at work. This study determined the sEMG characteristics between erector spinae and vastus lateralis during bending forward and squatting down tasks by analyzing the regularity of variation in sEMG frequency domain index-median frequency (MNF) in healthy subjects. The results indicate that sEMG activities in erector spinae are significantly higher than those in the right vastus lateralis during bending forward task. Instead, in squatting down task, sEMG activities in the right vastus lateralis are significantly greater than those in erector spinae. It also shows that the fatigue degree of low back caused by trunk bending is much deeper than that by squatting down. The ratio scope of one-order fitting values of MNF between erector spinae and vastus lateralis ranges from 0.87 to 1.72 among 80% of subjects during bending forward task and ranges from 0.31 to 1.11 during squatting down task. This study provides certain theoretical basis for using the strength of low back in a proper way to avoid getting it hurt in daily physical activities.